PENGARUH KEPAILITAN TERHADAP HARTA BERSAMA SUAMI ISTRI DITINJAU DARI PERSPEKTIF - Theda Febrina Subagia, Ni Komang; -, Marwanto; Rudy, Dewa Gde (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013, 2013)
Effect of bankruptcy on property with marital viewed from the perspectivehukum kepailitan. The problems that arise are related to how the concept of communityproperty in the legislation of law? and how the legal consequences of bankruptcyjudgment against the marital property of husband and wife?. The method of writingusing descriptive normative methods. The results of research related to the concept ofmarital property contained in Article 119 KUHPerdata and Article 35 paragraph (1)Undang Undang Perkawinan and in the event bankruptcy of the marital property ofhusband and wife, it will betreated as joint bankruptcy. So the conclusion of conceptmarital property in the KUHPerdata and Undang Undang Perkawinan havedifferences, both views of common property resources, the extent of union property, theexistence of private property after the marriage, the maintenance of marital property, aswell as the existence and function of mating in marital property agreement and the legaleffect of the decision bankruptcy of the marital property with husband and wife will betreated as joint bankruptcy case in accordance with Article 64 paragraph(1) of UndangUndang Kepailitan.
Keywords: Perspective, Marital Property, Judicial Review, Bankruptcy I. PENDAHULUAN